2010
DOI: 10.17221/1707-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Activities of N-acetyl-β-d-glucosaminidase and glutathione peroxidase in bovine colostrum and milk

Abstract: Parturition and post partum period are susceptible for antioxidative/oxidative imbalance as well as inflammatory processes related to either uterus or mammary gland. Fifteen Holstein-Friesian cows were used to examine the relationship between the antioxidant enzyme glutathione peroxidase (GSH-Px) and inflammatory enzyme N-acetyl-glucosaminidase (NAGase) in colostrum and milk during 12 days after parturition. Samples from each udder quarter were collected immediately after parturition, after 24 h and 48 h as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The various non‐enzymatic and enzymatic antioxidants present in the tissues as a part of anti‐oxidative defense mechanism of organisms serves the role of ROS scavenger. This response of the defense mechanism of organisms against stress results in increased activity of anti‐oxidative enzymes to combat loss of enzymes . From Table it might be observed that the APx activity increased to about 1.84‐fold in Pistia sp.…”
Section: Resultsmentioning
confidence: 97%
“…The various non‐enzymatic and enzymatic antioxidants present in the tissues as a part of anti‐oxidative defense mechanism of organisms serves the role of ROS scavenger. This response of the defense mechanism of organisms against stress results in increased activity of anti‐oxidative enzymes to combat loss of enzymes . From Table it might be observed that the APx activity increased to about 1.84‐fold in Pistia sp.…”
Section: Resultsmentioning
confidence: 97%